From Kingdom to Elitdom: Tradition and the Question of Relevant Education in Ethiopia - Woldeyes, Yirga Gelaw (Curtin University, 2013)
This study is a rigorous and critical analysis of the significance and relevance of tradition to modern education in Ethiopia. Based on the interpretation of empirical, historical and theoretical information, it demonstrates how the Ethiopian education system drew antagonistic relationship between education and tradition with the consequence of making the experience and interest of the majority of the population irrelevant to modernisation.